Multi-hazard upgrade decision making for critical infrastructure based on life-cycle cost criteria. - Jalayer, F.
The life-cycle cost can be regarded as a benchmark variable in decision making problems involving the retrofit and upgrading of existing structures. A critical infrastructure is often subjected to more than one hazard during its lifetime. Therefore, the problem of evaluating the life-cycle cost involves uncertainties in both loading and structural modeling parameters. The present study is a preliminary study aiming to calculate the expected life cycle cost for a critical infrastructure subjected to more than one hazard in its service lifetime. A methodology is presented that takes into account both the uncertainty in the occurence of future events due to different types of hazard and also the deterioration of the structure as a result of a series of events. In order to satisfy life safety conditions, the probability of exceeding the limit state of collapse is constrained to be smaller than an allowable threshold. Finally, the methodology is implemented in an illustrative numerical example which considers a structure subjected to both seismic hazard and blast hazard in both upgraded and non-upgraded configurations. It is demonstrated how expected life cycle cost can be used as a criterion to distinguish between the two choices while satisfying the life safety constraint.
Keywords: Life cycle cost analysis; Upgrade decision making; Risk analysis